The Role of Savings and Income Diversification in Households' Resilience Strategies: Evidence from Rural Vietnam - Manh Hung Do (Social Indicators Research, 2023)
Understanding households' resilience-building strategies is vital for the domains of humanitarian assistance, economic development, and poverty reduction, especially in the places where are vulnerable to shocks. In this study, we offer the first trial that takes into account the correlation between households' risk attitude and their resilience-building strategies, namely savings as an absorptive capacity and income diversification as an adaptive capacity. We examine the effects of these resilience strategies on reducing the impacts of shocks and poverty. We use a panel data of 1227 identical households for Vietnam in two waves of the Thailand–Vietnam Socio-Economic Panel project to investigate the above issues. We address the endogenous problems of households' risk attitude, savings, and income diversification. Our results show that more risk-averse households tend to save more and diversify their income portfolios. These precautionary strategies to build up their resilience capacity help prevent them from reducing consumption caused by shocks and from falling into poverty in absolute, relative, and multidimensional measures. We suggest that rural development policies in developing countries should focus on facilitating more income generation and employment opportunities. Furthermore, the development of rural education and infrastructure for information and communication technology should be taken into account of designing poverty reduction programs.
Keywords: C33; Q00; Q12; 300; Panel data; Absorptive capacity; Adaptive capacity; Instrumental variables